Combining sequential extraction and 3D fluorescence to investigate the behavior of antibiotic and polycyclic aromatic hydrocarbons during solar drying of sewage sludge. (July 2022) - Ezzariai, Amine; An-nori, Amal; El Fels, Loubna; Riboul, David; Merlina, Georges; Barret, Maialen; Lacroix, Marlène Z.; El Mejahed, Khalil; El Gharous, Mohamed; Bousquet-Melou, Alain; Kouisni, Lamfeddal; Patureau, Dominique; et al.
Abstract: Solar drying and liming are commonly used for sludge treatment, but little is known about their efficiency on antibiotics and Polycyclic Aromatic Hydrocarbons (PAHs) removal. This study aimed to investigate the removal of antibiotics and PAHs during solar drying of Limed Sludge (LS) and Non-Limed Sludge (NLS). Thus, organic matter fractionation and 3D fluorescence were used to assess the accessibility and the complexity of organic matter. 2 experiments have been conducted using LS and NLS for 45 days of drying in a pilot scale tunnel. Physicochemical results indicated significant decrease of water content (90%) for both sludge samples within 15 days of drying. For both treatments, the removal of total organic carbon and total nitrogen was low and similar for both treatments. Through this study, it has been confirmed that liming and drying contributed to a strong modification of the organic matter quality with an increase of its accessibility. On the other hand, drying alone increased the less accessible compartments, while the presence of lime affected the interconnexion between the organic matter pools. 3D fluorescence confirmed the obtained results and indicated that LS leads to obtaining more simple molecules in the most accessible compartments, while NLS leads to obtaining more complex molecules in the less accessible compartments. In addition, solar radiations and leaching may contribute to the significant removal ( p < 0.01) of roxithromycin, benzo(a)anthracene, chrysene, benzo[k]fluoranthene, benzo[a]pyrene, and benzo(g, h, i) perylene in the presence of lime. Furthermore, the evolution of organic matter pools in terms of accessibility and complexity may drive the bioavailability of these pollutants, leading to their significant removal. Graphical abstract: Image 1 Highlights: The lime addition leads to increase the accessibility of sludge organic matter. Significant removal of some antibiotics and PAHs was obtained after liming. The persistence of antibiotics and PAHs needs to be well considered. Fractionation leads to better understand the fate of antibiotics and PAHs.